The Economy as a Complex Spatial System Macro, Meso and Micro Perspectives (Springer Proceedings in Complexity,, 2018)
This book is open access under a CC BY-NC 4.0 license. This collected volume represents the final outcome of the COST Action IS1104 "The EU in the new complex geography of economic systems: models, tools and policy evaluation". Visualizing the EU as a complex and multi-layered network, the book is organized in three parts, each of them dealing with a different level of analysis: At the macro-level, Part I considers the interactions within large economic systems (regions or countries) involving trade, workers migration, and other factor movements. At the meso-level, Part II discusses interactions within specific but wide-ranging markets, with a focus on financial markets and banking systems. Lastly, at the micro-level, Part III explores the decision-making of single firms, especially in the context of location decisions.